tRNA gene diversity in the three domains of life - Fujishima, Kosuke; Kanai, Akio (Frontiers in Genetics, 2014)
Transfer RNA (tRNA) is widely known for its key role in decoding mRNA into protein. Despite their necessity and relatively short nucleotide sequences, a large diversity of gene structures and RNA secondary structures of pre-tRNAs and mature tRNAs have recently been discovered in the three domains of life. Growing evidences of disrupted tRNA genes in the genomes of Archaea reveals unique gene structures such as, intron-containing tRNA, split tRNA, and permuted tRNA. Coding sequence for these tRNAs are either separated with introns, fragmented, or permuted at the genome level. Although evolutionary scenario behind the tRNA gene disruption is still unclear, diversity of tRNA structure seems to be co-evolved with their processing enzyme, so-called RNA splicing endonuclease. Metazoan mitochondrial tRNAs (mtRNAs) are known for their unique lack of either one or two arms from the typical tRNA cloverleaf structure, while still maintaining functionality. Recently identified nematode-specific V-arm containing tRNAs (nev-tRNAs) possess long variable arms that are specific to eukaryotic class II tRNASer and tRNALeu but also decode class I tRNA codons. Moreover, many tRNA-like sequences have been found in the genomes of different organisms and viruses. Thus this review is aimed to cover the latest knowledge on tRNA gene diversity and further recapitulate the evolutionary and biological aspects that caused such uniqueness.